Analysis of Spiders’ Joint Kinematics and Driving Modes under Different Ground Conditions - Xin Hao; Wenxing Ma; Chunbao Liu; Yilei Li; Zhihui Qian; Luquan Ren; Lei Ren (Applied Bionics and Biomechanics)
Although the hydraulic transmission system in spider legs is well known, the spider’s mechanism of locomotion during different terrain conditions still need to be explored further. In this study, spider locomotion was observed in detail on three pavement test platforms: horizontal hard pavement, horizontal soft pavement, and sloped soft pavement. The movement characteristics and joint kinematics of Grammostola rosea legs were captured by high-speed cameras and Simi Motion 3D tracking software. These observations showed that the gait pattern was basically consistent with an alternating tetrapod gait; however, the pattern observed on the sloped soft pavement was slightly different from that of the two horizontal pavements. In particular, the duty factor of the spiders was 0.683 when walking on the horizontal hard pavement, 0.668 on the horizontal soft pavement, and 0.630 on the sloped soft pavement. The duty factor was greater than 60% in all three pavement environments, which was minimal when walking on the sloped soft pavement. This pattern showed that spiders might have superior stability when walking, but their stability decreased in the sloped soft pavement environment. The ranges of joint angles through the spiders’ gait cycles in every pavement environment were also analysed and compared. The findings showed that the hydraulically driven femur-patella and tibia-metatarsal joint angles varied widely, which confirmed that hydraulically driven joints had major functions and obvious effects on the walking process. The kinematic patterns identified in this study provide improved understanding of the hydraulic transmission mechanisms, the factors that affect motion stability, and the design of biomimetic systems.